2014
DOI: 10.1590/s0102-67202014000400013
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of cholecystocolic fistula

Abstract: IntroductionCholecystocolic fistula is a rare complication of gallbladder disease. Its clinical presentation is variable and nonspecific, and the diagnosis is made, mostly, incidentally during intraoperative maneuver. Cholecystectomy with closure of the fistula is considered the treatment of choice for the condition, with an increasingly reproducible tendency to the use of laparoscopy.AimTo describe the laparoscopic approach for cholecystocolic fistula and ratify its feasibility even with the unavailability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…[1][2][3] CCF is due to repeated inflammation and adhesive formation between the gallbladder and the colon. 2,4 The etiology of CCFs is diverse, including malignant tumors, trauma, postoperative complications, diverticular disease, and most frequently, complicated biliary lithiasis. 3,7,8 A sequence of events occurs in acute and chronic inflammation of many different causes, resulting in the inflammation of the adjacent colonic serosal surface and adhesion to the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3] CCF is due to repeated inflammation and adhesive formation between the gallbladder and the colon. 2,4 The etiology of CCFs is diverse, including malignant tumors, trauma, postoperative complications, diverticular disease, and most frequently, complicated biliary lithiasis. 3,7,8 A sequence of events occurs in acute and chronic inflammation of many different causes, resulting in the inflammation of the adjacent colonic serosal surface and adhesion to the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,12 Clinical symptoms of CCF include chronic diarrhea, abdominal pain, jaundice, fever, nausea, vomiting, steatorrhea, weight loss, hemorrhagic diathesis, and bowel obstruction. [2][3][4] Various diagnostic methods can be used, such as abdominal ultrasonography, CT, magnetic resonance imaging, ERCP, and barium angiography. 7,8 However, in most cases, preoperative diagnosis is difficult because of nonspecific clinical symptoms, which are found incidentally during laparoscopic surgery and is a major cause of open conversion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The one-stage procedure is associated with reportedly higher morbidity and mortality, and longer operating times, when compared to simple enterotomy 7–9. Laparoscopic10 and endoscopic11 management of cholecystoenteric fistula have also been described. However, findings from autopsy and at re-operation have demonstrated that cholecystoenteric fistulas can close spontaneously, unless there is persistent cholelithiasis 8 12.…”
Section: Discussionmentioning
confidence: 99%